Picosecond alexandrite laser is superior to Q-switched Nd:YAG laser in treatment of minocycline-induced hyperpigmentation: A case study and review of the literature. (17th November 2018) - Barrett, Tom; de Zwaan, Sally
ABSTRACT: Background: Minocycline is a commonly prescribed tetracycline antibiotic used for the treatment of a number of dermatological conditions including acne and rosacea. Long-term adverse effects of minocycline include cutaneous hyperpigmentation. Various treatment options have been suggested for the treatment of minocycline pigmentation. We report a case of a patient on long-term low-dose minocycline for the treatment of rosacea with type III minocycline hyperpigmentation. A comparison was made between Q-Switch Nd:YAG and picosecond laser over a nine 9-period with treatments spaced 1 month apart, with a clearance in the patient pigmentation after four treatments with picosecond laser.